Denning ecology of Conepatus chinga (Carnivora: Mephitidae) in a grassland relict of central Argentina - Castillo, Diego Fabian (2013)
In order to investigate the factors affecting den site selection in Conepatus chinga, we identified and characterized 199 (males: n = 108, females: n = 91) dens used by 7 radio-tracked skunks from August 2002 to October 2005 in a protected area of the Argentine Pampas grassland. Skunks frequently reused dens (25.1%), without significant differences between sexes. Although C. chinga are solitary animals, our data indicate that males and females may be able to share dens, presumably in the breeding season. Den sites were not homogeneously distributed within an animal’s home range, being the density in core areas greater than in middle and border regions of home ranges. This study confirmed that C. chinga selects specific habitat characteristics for its den sites and suggests that the access to prey is a major factor in their selection.